Big Nate : nailed it! - Peirce, Lincoln (Big Nate, 2023)
"You can't win 'em all-- especially when you're slumping sixth-grader Nate Wright. Stuck in a cycle of misfortune, our hero finds an unlikely good luck charm... and suddenly, he can do no wrong! He finds a $20 bill, scores a C+ on his social studies test (nailed it!), and even lands a movie date with the captain of the cheer squad. But the high times can't last forever. Before long, Nate's epic hot streak has gone ice cold, thanks to all-time hair crisis, a great escape by the class gerbil, and a no-holds-barred chess match versus... a CAT. Welcome to the riotous world of Big Nate, where chaos is the default setting and Nate's learning the secret of survival: sometimes it's better to be lucky than good!"--Back cover.